Pancreatopleural fistula as a complication of necrotizing pancreatitis (clinical case) - V.I. Desyateryk; O.V. Kotov; S.P. Mikhno; Ye.O. Okhotnik; M.P. Krasnov (Medičnì Perspektivi)
Acute pancreatitis is a disease that is accompanied by systemic inflammatory response syndrome and polysystemic dysfunction. Often acute pancreatitis leads to damage to various organs, including: pleura, mediastinum, cardiovascular structures. These complications cause difficulties in diagnosing and treating patients. In this review, we discuss the complications of acute pancreatitis, focusing on the diagnosis and treatment of pancreatopleural fistulas. Pancreatopleural fistula is a rather rare complication observed in patients with both acute and chronic pancreatitis due to traumatic or iatrogenic damage to the pancreatic duct. Conservative treatment with ocreatid combined with stenting of the pancreatic duct currently makes it possible to achieve closure of the fistula in 31-45% of cases, surgical intervention – in 80-90% of cases. The clinical case presented in this article demonstrates the successful treatment of this difficult complication of acute pancreatitis. The authors emphasized the need for timely diagnosis of this condition, as delaying adequate treatment can worsen the prognosis of recovery of patients with pancreatopleural fistulae.